2020
DOI: 10.3390/nu13010020
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Consumers’ Food Practices during the COVID-19 Lockdown, Implications for Diet Quality and the Food System: A Cross-Continental Comparison

Abstract: COVID-19 has led to dramatic societal changes. Differing movement restrictions across countries have affected changes in consumers’ food practices, with a potentially detrimental impact on their health and food systems. To investigate this, this research explored changes in consumers’ food practices during the initial COVID-19 phase and assessed the impact of location on these changes. A sample of 2360 adults from three continents (Island of Ireland (IOI), Great Britain (GB), United States (USA), and New Zeala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
127
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(139 citation statements)
references
References 63 publications
(103 reference statements)
8
127
1
3
Order By: Relevance
“…However, they were also more likely to report increasing their canned fruit and vegetable consumption compared with food-secure respondents. These findings are consistent with other studies that have found increases in the consumption of shelf-stable foods and decreases in that of fresh foods since the beginning of the COVID-19 pandemic [35,36,[44][45][46][47]. Several studies have also found that a higher proportion of food-insecure individuals report buying less fresh foods [35,36].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, they were also more likely to report increasing their canned fruit and vegetable consumption compared with food-secure respondents. These findings are consistent with other studies that have found increases in the consumption of shelf-stable foods and decreases in that of fresh foods since the beginning of the COVID-19 pandemic [35,36,[44][45][46][47]. Several studies have also found that a higher proportion of food-insecure individuals report buying less fresh foods [35,36].…”
Section: Discussionsupporting
confidence: 91%
“…Two studies in Italy focused specifically on change in fresh fruit and vegetable intake: in one study, 18% of the respondents reported consuming less fresh vegetables, and about 17% reported consuming less fresh fruit, while in the other study 8.7% of the respondents reported consuming less fresh fruits and vegetables [45,46]. In a study that included respondents from four Western countries, the average portions of fruits and vegetables consumed per day actually increased from before the pandemic to during the pandemic [47]. No studies to date have compared changes in fruit and vegetable intake between food-secure and food-insecure individuals, but one study of U.S. emerging adults found that food-insecure respondents had significantly lower home availability of fruits and vegetables compared with food-secure respondents [48].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we did not collect information on the educational or socioeconomic level of participants. Many of the cross-sectional studies conducted during the pandemic aimed to analyze modifications in health-related behaviors [8,9,33,[51][52][53] report an over representation of higher educated people, and in many cases, younger age groups are overrepresented as well. In our study, we cannot assess the potential unequal distribution regarding the level of education.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study in India found that due to the lockdown policies, work pressure is reduced and it has helped people with type 2 diabetes improve their medication adherence and physical activity at home, thereby improving their blood sugar control (24). It seems that the changes in healthy lifestyle caused by the pandemic are varied in different countries (25), but many scholars still suggest that effective home physical activity and healthy eating strategies should be developed to help chronic patients maintain their health status (26,27). During this period, telephone coaching or counseling can be a suitable and effective method as well (28,29), and many studies have even confirmed the effectiveness of telephone coaching before the pandemic (30,31).…”
Section: Discussionmentioning
confidence: 99%